Impact of Organizational Justice on Learning Organization: An Empirical Investigation of Banking Sector of Pakistan - Farrukh, Muhammad; Syed , Nida; Saeed , Arfa (Asian Journal of Empirical Research, 2014)
The primary purpose of this research is to examine the association between learning organization and organizational justice in the banking sector of Pakistan. This research also investigates that which type of organizational justice is more effective in banking sector of Pakistan. The findings of this paper show that organizational justice has a significant impact on learning organization. Furthermore, it is also found that distributive justice is more effective than other dimensions of justice.